Tools for network monitoring and network debugging in LINUX - Petrov, Georgi; Bogomilov, Ivan (Yearbook Telecommunications, 2017)
This publication provides an overview of network monitoring and troubleshooting methods in IP networks used by network architects and engineers. Knowing some basic tools for testing and monitoring traffic in IP networks in Linux is important in building, expanding and reconfiguring network infrastructure. Integrated, ready-made functional tools in administrative scripts are the basis for creating most effective and powerful tools for checking and troubleshooting network infrastructure.